Postoperative brachytherapy alone for 217 patients with early-stage oral cavity squamous cell carcinoma - C. Schweizer; V. Strnad; M. Lotter; S. Kreppner; R. Merten; R. Fietkau; A. Karius (Clinical and Translational Radiation Oncology)
Introduction: Postoperative radiotherapy is generally recommended for pT1/2pN0 squamous cell carcinoma of the oral cavity (OSCC) if risk factors are present. Prospective studies are missing. Interventional radiotherapy offers a precise dose application. In this paper we analyze long-term efficacy and toxicity in a large single-center cohort of patients with early OSCC receiving sole postoperative brachytherapy (BT). Material and methods: From 1998 to 2023, 217 patients were postoperatively treated with sole BT in our institute. The median follow-up was 110 months (range: 2–316). The primary objective was local control. Secondary outcomes were overall survival, cancer specific survival, and toxicity. Results: The local recurrence rates for 12, 24, and 60 months were 7.1 %, 9.1 %, and 12.6 %. The disease-free survival was 89.7 %, 86.1 %, and 79.3 %. The overall survival rates at 12, 24, and 60 months were 94.4 %, 89.6 %, and 77.9 %. The cancer-specific survival was 97.1 %, 96.6 %, and 92.9 %, respectively. At two years, the rate of regional recurrence was 8.3 %. Patients without neck dissection had a significantly increased risk for lymph node recurrence (p = 0.025). Side effects ≥ grade 3 were seen in 14 % (30/217). 17 % (37/217) of patients developed a soft tissue necrosis (STN). Osteoradionecrosis (ORN) was seen in 7 % (15/217) of patients. A target volume > 15 cm3 was significantly associated with the occurrence of STN (p = 0.011) and ORN (p = 0.004). Conclusions: Postoperative interventional radiotherapy for previously not irradiated patients with early-stage OSCC is a safe and efficient treatment. Randomized trials are needed to compare these results to omission of postoperative radiotherapy as well as external beam radiotherapy.